ACTIVITIES OF THE GUARANTEE FUND FOR SERVICING PUBLIC DEBT - Payziyeva Komila (KONFERENSIYALAR, 2025)
This paper explores the role and activities of the Guarantee Fundin servicing public debt, highlighting its importance in ensuring fiscal stabilityand investor confidence. The Guarantee Fund serves as a financial mechanismthat mitigates the risk associated with public debt by providing guarantees fordebt repayments. This study examines the structure, functions, and operationalprocedures of the Guarantee Fund, along with its impact on public debtmanagement. Through an analysis of case studies and empirical data, the paperprovides insights into the effectiveness of the Guarantee Fund in maintainingsovereign credit ratings and promoting sustainable economic growth. Thefindings underscore the significance of the Guarantee Fund in managingfinancial risks and enhancing the credibility of public debt issuances.